Moderation of Extracurricular Activities in Influencing Diamond Fraud on Academic Fraud Behaviour - Nina Farliana; Ratieh Widhiastuti; Wisudani Rahmaningtyas; Atika Nurdiana (Jurnal Pendidikan dan Pengajaran, 2022)
The number of students who commit academic fraud is a behaviour that is not commendable and should not occur in the academic environment. This study aims to test whether there is an influence between pressure, opportunity, rationalization, and ability on academic cheating behaviour with extracurricular activities as a moderating variable. This study uses a quantitative approach. The population in this study was 7.029. Samples were taken using the Slovin formula for as many as 379 students, and the sampling technique used proportional random sampling. Methods of data collection using a questionnaire. The data analysis method used is descriptive statistical analysis and Moderated Regression Analysis (MRA). The study results show that pressure positively affects academic cheating behaviour by 11.36%. An opportunity has a positive effect on academic cheating behaviour by 5.52%. Then, Rationalization has a positive effect on academic cheating behaviour by 18.84%. The ability has a positive effect on academic cheating behaviour by 42.77%. The implication is extracurricular activities can strengthen the influence of pressure, rationalization and ability on academic cheating behaviour. However, unable to moderate the effect of opportunity on academic cheating. This research suggests that exam supervisors can tighten supervision, and students can foster self-confidence.